Brick by Brick : Elevating Data Driven Culture by measuring WOW factor - Lorenz, František (2024)
In today's rapidly evolving business landscape, the significance of data and analytics in driving decision-making and operational efficiency cannot be undervalued. This di-ploma thesis investigates the transformation of a traditional model production unit within a large corporate company into a data-driven entity, aligned with the enter-prise's strategic direction. The study focuses on defining a comprehensive data and ana-lytics strategy, leveraging advanced data management techniques, and measuring the effectiveness of marketing materials through a "WOW factor." The methodology in-cludes the integration of causal impact analysis using Databricks and Power BI as one example, and outline the need for development of IoT-enabled models for real-time tracking of marketing materials. The results demonstrate the feasibility and benefits of a data-driven approach, providing actionable insights that enhance marketing effective-ness and operational efficiency. This transformation fosters a cultural shift towards more enlightened ways of working, ensuring a prosperous future for the Model Produc-tion unit.